PENERAPAN TERAPI RELAKSASI OTOT PROGRESSIF PADA KLIEN ANSIETAS DI KELURAHAN CIWARINGIN, BOGOR - syisnawati, Syisnawati; Keliat, Budi Anna; Eka, Yossie Susanti (Universitas Islam Negeri Alauddin Makassar, 2017)
Anxiety is a condition or feeling of uncertainty felt by someone who can be caused by various factors, including the problem of physical disorders as has been proved that the person's general health has a real effect as a predisposition to anxiety Clients with chronic disease often experience anxiety. This final scientific work aims to report the theraupetic application of progressive muscle relaxation therapy to clients with anxiety with chronic disease. This final scientific work using by interpersonal model of Peplau to 16 clients. Results of the application of progressive muscle relaxation therapy showed the largest decrease in the signs and symptoms of physiological aspects and an ncrease in the ability of the clients. Combination therapy generalist progressive muscle relaxation is recommended to be given clients with chronic illnesses anxiety both in public health centers, hospitals and in the community.